Factors associated with implantable cardioverter defibrillators appropriate therapy in cardiac sarcoidosis: a meta-analysis: Implantable cardioverter defibrillators in cardiac sarcoidosis - Azoulay, Levi-Dan; Waintraub, Xavier; Haroche, Julien; Amoura, Zahir; Cohen Aubart, Fleur (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Patients with cardiac sarcoidosis (CS) are at increased risk of atrioventricular blocks, ventricular arrhythmias, and sudden cardiac death. Objectives We aimed to investigate the characteristics associated with appropriate therapy in implantable cardiac defibrillator (ICD) -implanted CS patients. Methods: We performed a PubMed and Web of Science search for studies reporting patients with CS who underwent an ICD implantation. The primary criterion was an appropriate therapy. Results: We screened 705 studies, of which 5 were included in the final analysis. We conducted a meta-analysis including 464 patients (mean age 55 years, 282 males (60%)). The mean follow-up was 3.5 years. Among the 464 patients, 180 received an appropriate therapy (39%). Patients who received an appropriate therapy were younger (-3.33, 95% confidence interval (CI) -6.42 to -0.23, p=0.004), were more likely to be male (OR 2.06, 95% CI 1.37-3.09, p=0.0005), had a lower left ventricular ejection fraction (LVEF) (-10.5, 95% CI -18.23 to -2.78, p=0.008), had a higher rate of complete heart block (OR 2.19, 95% CI 1.20 to 3.99, p=0.01), and more frequently had ventricular pacing (OR 6.44 95% CI 2.57 to 16.16, p<0.0001). Conclusions: Appropriate ICD therapy during CS is associated with young age, male sex, low LVEF, history of complete heart block, and ventricular pacing.